DAMPAK KONFLIK KELUARGA-PEKERJAAN DAN MOTIVASI INTRINSIK TERHADAP KINERJA KERJA - Silky Pentanesia Mantik; Sunjoyo Sunjoyo (Universitas Kristen Maranatha, 2018)
This study aimed to determine the effect of work-family conflict and intrinsic motivation on job performance. The data used in this research is primary data which is taken by disseminating the questionnaire. Subjects in this research are the employees in 3 companies which are, PT X and BPR X, located in Bandung and Bank X, located in Semarang. A total 206 usable questionnaires were collected. Samples are selected by using probability sampling and convenience sampling method. The analytical method used in this research is multiple linear regressions. The result showed that only one hypotheses was supported from two hypotheses. The implication of this study is discussed and the suggested research is advanced during the process. Keywords: Work-Family Conflict, Intrinsic Motivation, Job Performance